The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0112082
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model of the hUbA1-UbcH10 Quaternary Complex: In Silico and Experimental Analysis of the Protein-Protein Interactions between E1, E2 and Ubiquitin

Abstract: UbcH10 is a component of the Ubiquitin Conjugation Enzymes (Ubc; E2) involved in the ubiquitination cascade controlling the cell cycle progression, whereby ubiquitin, activated by E1, is transferred through E2 to the target protein with the involvement of E3 enzymes. In this work we propose the first three dimensional model of the tetrameric complex formed by the human UbA1 (E1), two ubiquitin molecules and UbcH10 (E2), leading to the transthiolation reaction. The 3D model was built up by using an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…MLN4924 is clearly inferior to the other two ligands, mainly because of its missing hydroxyl group and the resulting inability to form electrostatic interactions in the bound state on a comparable level. Since these results are in good qualitative agreement with the experimentally measured inhibitory values, MLN7243 was also investigated as the best ligand on the basis of the human UBA1 homology model published earlier (Correale et al, 2014). In this complex the electrostatic contribution was found to be slightly less favorable.…”
Section: Computational Analyses Of Inhibitors Complexed To Uba1supporting
confidence: 66%
See 1 more Smart Citation
“…MLN4924 is clearly inferior to the other two ligands, mainly because of its missing hydroxyl group and the resulting inability to form electrostatic interactions in the bound state on a comparable level. Since these results are in good qualitative agreement with the experimentally measured inhibitory values, MLN7243 was also investigated as the best ligand on the basis of the human UBA1 homology model published earlier (Correale et al, 2014). In this complex the electrostatic contribution was found to be slightly less favorable.…”
Section: Computational Analyses Of Inhibitors Complexed To Uba1supporting
confidence: 66%
“…Alternate locations were selected after visual inspection and the system was protonated using Protonate3D (Labute, 2009) with default settings at pH 7.4 and locally minimized with the Amber12:EHT force field implemented in MOE using an rms gradient of 0.1 kcal/(mol•Å ). Furthermore, a complex of human UBA1 and MLN7243 was generated on the basis of the published homology model of human UBA1 without ligand (Correale et al, 2014). After preparation of the protein according to the presented workflow and modeling the side chains of M505 and R551 (corresponding to N471 and K519 in yeast Uba1) in conformations not blocking the binding pocket, MLN7243 was placed therein, in analogy to the binding mode observed in the corresponding yeast Uba1 complex structure.…”
Section: Star+methods Key Resources Table Contact For Reagent and Resource Sharingmentioning
confidence: 99%
“… 96 , 104 , 109 In each case, the thioester-linked ubiquitin is bordered by the E2, the FCCH domain, and ubiquitin in the adenylation site, although the models differ somewhat. In two cases the thioester-linked ubiquitin contacts the FCCH domain, 104 , 109 while in another case the thioester-linked ubiquitin contacts the E2. 96 In the later case, ubiquitin was positioned in a similar but not identical conformation to the closed E2∼ubiquitin conformation (see below).…”
Section: E1 Activating Enzymesmentioning
confidence: 99%
“…In human, ten UBA orthologues have been identified that can activate ubiquitin or UBLs. Ubiquitin-like modifier-activating enzyme 1 (UBA1) is mainly responsible for ubiquitin-activation and can also activate the NEDD8 UBL peptide [26][27][28]. UBA2 (or UBLE1B) is also known as SUMO-activating enzyme subunit 2 (SAE2), and activates the SUMO UBL peptide as heterodimer with SAE1 [29].…”
Section: E1 Ubiquitin-activating Enzymes (Uba)mentioning
confidence: 99%